Rapidly Evolving Landscape and Future Horizons in Hepatocellular Carcinoma in the Era of Immuno-Oncology - Kang, Sandra Mirie; Khalil, Lana; El-Rayes, Bassel F.; Akce, Mehmet (Frontiers in Oncology, 2022)
Hepatocellular carcinoma (HCC) is a serious global health problem as one of the leading causes of cancer-related death worldwide. Systemic therapy for advanced HCC has progressed with the development of molecular targeted agents, however survival benefits remain modest. More recently, immune checkpoint inhibitors (ICI) have emerged and exhibited promising therapeutic benefits in a subset of patients. Physiologically, the intrinsic microenvironment in the liver is immunosuppressive, which represents a major obstacle for effective immune therapies in primary and secondary liver malignancies. For this reason, combination therapies that can overcome immune inhibitory mechanisms and enhance the immune response are a rationale approach for drug development in HCC. A recent example is the combination of the anti-PD-L1 antibody (atezolizumab) and anti-VEGF-A antibody (bevacizumab), which has shown significant improvement in survival as compared to standard of care in the first-line treatment for HCC. Other immunotherapy approaches including cancer vaccines and adoptive cell therapy are also under investigation. This review summarizes the key trials leading to our current HCC treatment options and provides an overview of future immune-based strategies in development.